PENERAPAN MODEL PEMBELAJARAN INKUIRI DIPADU DENGAN MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA KELAS XI MIPA 2 SMA N 6 SURAKARTA SEMESTER 2 TAHUN PELAJARAN 2014/2015 - Windy Purwati; Slamet Santosa; Yudi Rinanto (Universitas Sebelas Maret, 2016)
This research was aimed to improve cognitive ability of student class XI MIPA 2 SMA Negeri 6 Surakarta academic year 2014/2015 through the implementation of inquiry learning model that is combined with mind mapping. This research was classroom action research that divided into two cycles. The subject of this research is the student of XI MIPA 2 SMA Negeri 6 Surakarta academic year 2014/2015. The method of data collection through tes, observation, interviews, and documentation. The data is analyzed with descriptive analytical technique and validated by triangulation technique.The result show that student cognitive ability is increased in pre-cycle, cycle I, cycle II. The average of students cognitive ability increase from pre-cycle 35,01 % to 55,21 % at cycle I, and 78,02 % at cycle II. Remembering aspect increase from 40,40 % to 88,88 %. Understanding aspect increase from 37,87 % to 82,31 %. Applying aspect increase from 46,46% to 82,82 %. Analyzing aspect increase from 29,29 % to 73,73 %. Evaluating aspect increase from 26,76 % to 71,20 %. Creating aspect increase from 29,29 % to 69,18 %. This research’s conclutions is the implementation of inquiry learning model that combined with mind mapping can improve cognitive ability of the student class XI MIPA 2 SMA Negeri 6 Surakarta. Keywords : Inquiry, Mind Mapping, Cognitive Ability